Estimated Annual Economic Burden of Dry Eye Disease Based on a Multi-Center Analysis in China: A Retrospective Study - Yang, Wanju; Luo, Yanzhu; Wu, Shangcao; Niu, Xiaoxia; Yan, Yanshuang; Qiao, Chen; Ming, Wei; Zhang, Ying; Wang, Haoyu; Chen, Dan; Qi, Mengying; Ke, Lan; et al. (Frontiers in Medicine, 2021)
Purpose: To conduct a multi-center analysis and assess the economic burden due to dry eye disease (DED) in China. Design: A retrospective and cross-sectional study. Methods: Patients (n = 598) with diagnosed DED were recruited from 3 eye centers (in central, southeast, and northeast China) from 1 January 2018 to 31 December 2018. Data were collected regarding the examination, pharmacological therapy, and non-pharmacological therapy fees. Sub-group analyses were stratified by eye center, DED severity, types of DED, number of visits to physicians, and residential area. A logistic regression analysis was conducted to investigate the variables influencing total costs. Results: The per capita costs devoted to DED at the 3 centers were 422.6, 391.3, and 265.4 USD, respectively. The costs of non-pharmacological therapy accounted the largest part in three centers (75.6, 76.4, 76.5%, respectively). Patients with severe DED sustained the largest economic burden. Patients with mixed type of DED spent the most comparing to patients with either evaporative or aqueous-deficient types of DED. Patients spent more during the first visit compared with subsequent visits. Patients living in urban areas spent significantly more than did those living in rural areas (P = 0.001). The logistics regression analysis showed that total costs were significantly influenced by DED severity, number of visits to physicians, and area of residence (beta = 2.83, 0.83, 1.48; P < 0.0001). Conclusions: DED is a chronic ocular disease that timely non-cost counseling, early diagnosis, and efficacious treatment can reduce its economic burden on patients and the society.